SCIENTIFIC-METHODIC APPARATUS FORECASTING PARAMETERS OF THE SHIPPING EQUIPMENT - Дмитрієв, А. А.; Якусевич, Ю. Г.; Чебан, В. І. (Science-based technologies, 2019)
The article analyzes the methods of forecasting technical parameters of ship equipment. These methods are analyzed in terms of the possibility of forecasting the technical condition of marine equipment in conditions of use of vessels on transoceanic flights. The issues of the development of new methods of technical equipment operation on the basis of the application of modern automated procedures for determination of periodicity and scope of diagnostics are also considered. The article argues that the implementation of pre-planned volumes of maintenance and repair works in due time in most cases does not provide the desired reliability and leads to an increase in post-repair failures. In addition, the experience of operating water transport means that the adopted approach to the maintenance and repair system leads to significant over-consumption of material and financial resources. Therefore, a promising system of diagnostic provision of vessels should take advantage of the existing capabilities of traditionally measured parameters of the work process, as well as physical methods and means of diagnostics with prediction of parameters of the technical condition of equipment for water transport. In this aspect, the development of new methods for the technical operation of equipment, based on the use of modern automated procedures for determining the frequency and scope of diagnosis is relevant. The effectiveness of the diagnostic program is increased when, at the same content of control operations, the tasks of forecasting changes in the technical condition of equipment in future moments of time are solved. The forecasting program is the basis of realization of the system of technical maintenance of water transport facilities on the actual condition.